The spectral model of personal wellbeing and the validity of the Personal Wellbeing Spectral Questionnaire - Oláh, Attila; Bagdi, Bella; Vargha, András (Frontiers in Psychology, 2026)
IntroductionPersonal wellbeing is a multidimensional construct encompassing emotional, psychological, social, and spiritual aspects. To capture this complexity, we introduce the Personal Wellbeing Spectrum Theory, which organizes these dimensions into two higher-order domains: internal wellbeing (emotional and psychological) and external wellbeing (social and spiritual). The paper aimed to conceptualize this theory and to develop and validate the Personal Wellbeing Spectrum Questionnaire (PWBSQ), a tool designed to operationalize the model.MethodsThe structural validity of PWBSQ was examined in a large online sample (n = 11,686) using confirmatory factor analysis, and the hierarchical model was tested in three additional independent samples. Reliability and measurement invariance across sociodemographic groups were assessed. Substantive validity was evaluated through associations with established measures, including the Positivity Scale, Diener Flourishing Scale, Huppert Flourishing Scale, Values in Action Inventory, Mental Health Test, and the PERMA model.ResultsThe hierarchical model demonstrated good fit across multiple samples (RMSEA around 0.06, SRMR round 0.04, CFI and TLI around 0.95), with consistent reliability (α and ω > 0.79). Measurement invariance was supported across five sociodemographic variables. The questionnaire showed meaningful associations with subjective financial situation, gender, education, and family characteristics, while marital status and occupation had only minor effects.DiscussionFindings confirm the Personal Wellbeing Spectrum Theory and support the PWBSQ as a reliable and valid instrument for assessing multidimensional wellbeing. This tool provides researchers and practitioners with a comprehensive measure of personal wellbeing that can be applied across diverse populations, facilitating both theoretical development and practical assessment in health and social sciences.